Pemanfaatan Youtube dalam Pembelajaran Bahasa Indonesia di Perguruan Tinggi pada Kurikulum MBKM - Ilmatus Sa’diyah; Rizki Romadhoni Sandy; Eliezer M. Putra Siaturi; Athallah Bariq Hidayat (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The development off the times, the human need for technology cannot be abandoned. One of them is you tube. You Tube is a website where users can watch, upload, and share videos. The existence of you tube is a medium that can help the implementation of education now. However, its effect on students' Indonesian language skills is still a question. Therefore,the researchers tried to find the answer by conducting this research. This research used a questionnaire method with a Likert scale as the answer model. Then the validity test using SPSS and response analysis from the results of filling out the Likert scale answers. After the research, data were obtained from respondents, most of whom agreed with the hypothesis that had been proposed by the researchers. Finally, the researchers concluded that the existence of YouTube has an effect on Indonesian language skills.